A Study of Rockburst Hazard Evaluation Method in Coal Mine - Zhijie Wen; Xiao Wang; Yunliang Tan; Hualei Zhang; Wanpeng Huang; Qinghai Li (Shock and Vibration)
With the increasing of coal mining depth, the mining conditions are deteriorating, and dynamic hazard is becoming more likely to happen. This paper analyzes the relations and differences between rockburst in the coal mine and rockburst in the metal mine. It divides coal mine rockburst into two types including static loading type during roadway excavation process and dynamic loading type during mining face advancing. It proposes the correlation between the formation process of rockburst and the evolution of overlying strata spatial structure of the stope, criterion of rockburst occurrence, new classification, and predictive evaluation method for rockburst hazard that rockburst damage evaluation (RDE) = released energy capacity (REC)/absorbed energy capacity (AEC). Based on the relationship between RDE value and its corresponding level of rockburst hazard, the rockburst hazard can be divided into five types and evaluation index of each type can be achieved. Then the ongoing rockburst damage level can be classified in one of the five types, and the relative parameters, such as hazard extent, controlling measures also can be achieved. This new quantitative method could not only assess the impacting direction of rockburst occurrence, but also verify the effect of preventive measures for rockburst.